2022
DOI: 10.3390/ma15124343
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Heat Treatment on the Mechanical Properties and Corrosion Resistance of the Ultrafine-Grained AA7075 Obtained by Hydrostatic Extrusion

Abstract: In this paper, the corrosion resistance and mechanical properties of the 7075 aluminum alloy are studied. The alloy was deformed by hydrostatic extrusion and then aged both naturally and artificially. Results are compared with those of coarse-grained material subjected to T6 heat treatment. The aim of the research is to find the optimal correlation between the mechanical properties and the corrosion resistance of the alloy. To this end, static tensile tests with subsequent fractography, open circuit potential,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Some studies to date explored the corrosion behavior of 7075 alloy [ 12 , 13 , 14 , 15 , 16 ]. Marta Orłowska et al studied the impact of heat treatment on the mechanical properties and corrosion resistance of ultra-fine-grained 7075 alloy and found that plastic deformation increased susceptibility to corrosion due to an increase in grain boundaries [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies to date explored the corrosion behavior of 7075 alloy [ 12 , 13 , 14 , 15 , 16 ]. Marta Orłowska et al studied the impact of heat treatment on the mechanical properties and corrosion resistance of ultra-fine-grained 7075 alloy and found that plastic deformation increased susceptibility to corrosion due to an increase in grain boundaries [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies to date explored the corrosion behavior of 7075 alloy [ 12 , 13 , 14 , 15 , 16 ]. Marta Orłowska et al studied the impact of heat treatment on the mechanical properties and corrosion resistance of ultra-fine-grained 7075 alloy and found that plastic deformation increased susceptibility to corrosion due to an increase in grain boundaries [ 12 ]. Liwei Wang et al studied the corrosion evolution of high-strength aluminum alloys in a solution and a thin electrolyte layer containing Cl − and found that large corrosion cavities with limited underlying microcracks were formed [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this paper adopts a more comprehensive approach, and attempts to correlate appropriate heat treatment of 7xxx AAs that have undergone HE with the development of high mechanical strength and high resistance to corrosion in an aggressive environment. This work is a continuation of our previous work, where the influence of heat treatment on the single-stepped hydrostatically extruded AA7075 was investigated [20].…”
Section: Introductionmentioning
confidence: 89%
“…[17] It is well known that GP zones and η´precipitates can considerably improve the strength of EN AW-7075 alloy, while coarse η precipitates detrimentally affect the hardening of this alloy. [22,23] Additionally, during the growth of coarse η precipitates, the flux of solute atoms toward formed precipitates occurs, resulting in the depletion of alloying elements in the vicinity of coarse precipitates and eventually the formation of precipitate-free zones (PFZs) in the microstructure. [12,14] It was reported that these PFZs can adversely affect the mechanical properties of EN AW-7075 alloy.…”
mentioning
confidence: 99%